From the cradle to the grave - Koliński, Rafał; Kolińska, Xenia (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
From the cradle to the grave, we are accompanied by the concepts of mortality and immortal- ity. We experience the first as humans but ascribe, unknown to us, the state of eternal being to the gods. In various models of the universe, death may mean the end of everything, a new beginning, or a state of waiting to join the ranks of the Immortals. In Mesopotamia, death means Perduring; souls of the dead were confined to Underworld, where they lasted in dark - ness, suffering thirst and hunger. At the beginning of the 2 nd millennium BC in Mesopotamia the attitude towards the dead is changing significantly. Cult of ancestors and repeated offerings to dead were meant to improve their condition, and, in turn, secure their support to the living. The GP26 chamber tomb discovered at the Tell Arbid site in northeastern Syria in 2009 by archaeologists of the Institute of Prehistory, Adam Mickiewicz University, is a perfect illustration of these changes. The underground chamber tomb built next to the house became the resting place of three generations of its inhabitants, judging from the fact that at least 15 people were buried there successively. Prestigious grave gifts testify to the wealth of the family, and the finds of sacrificial vessels and animal bones illustrate ceremonies performed during the funeral. The tomb was ritually closed by burying the dog in the shaft leading to its chamber. The tomb was avoided being robbed in antiquity, thanks to which archaeologists from the Adam Mickiewicz University could study it and shed light on the beliefs and splendor of the inhabitants of northern Mesopotamia dating back almost 4,000 years.
Keywords: Mesopotamia; Middle Bronze Age; burial customs; chamber graves